(3CfSGH GdCTQGa fSH Jejes - (3GdHdGPQj, CMeO Hf jMji Hf LGHQ, J(B279(3g`s
(3ChdgG (B:s
(3fSH hdO eQI Hf CO Hf WGHNI hhdO eQI Hf CO Hf WGHNI Jeje Hf eQI hCeg GdTYjQGA HfJ VHI Hf CO hge aj Hfj ebGYSs
(3BNQgG (B:s
(3aBJGg hBhGg MJi UdM hNOeJg GHfJg aPcQgG aj TYQg hQKi aVGdI Mjf eGJ Je fSH hdO GdjGS Hf eVQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 267s
(3eYLe GdeDdajf(B: 1 / 322s
(3cTa GdXfhf(B: 1 / 179s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs